Coenzyme Q10 Activates the Antioxidant Machinery and Inhibits the Inflammatory and Apoptotic Cascades Against Lead Acetate-Induced Renal Injury in Rats - AL-Megrin, Wafa A.; Soliman, Doaa; Kassab, Rami B.; Metwally, Dina M.; Ahmed E. Abdel Moneim,; El-Khadragy, Manal F. (Frontiers in Physiology, 2020)
The kidney is among the metabolic organs most susceptible to injury, particularly following exposure to xenobiotics and heavy metals. We aimed to explore the potential protective impacts of coenzyme Q10 (CoQ10) on lead acetate (PbAc)-induced nephrotoxicity in rats. Four experimental groups (n=7) were applied as follows: control group, CoQ10 alone (10 mg/kg), PbAc alone (20 mg/kg), and PbAc with CoQ10. Exposure to PbAc led to the accumulation of Pb in the kidney and increased urea and creatinine serum levels. The deposition of Pb coupled with the elevation of malondialdehyde and nitrate/nitrite levels along with the upregulation of inducible nitric oxide synthase. Additionally, upon PbAc poisoning, glutathione content and the antioxidant enzymes were depleted along with the downregulation of Nrf2 and HO-1 expression. Moreover, PbAc injection increased the protein and mRNA levels of pro-inflammatory cytokines namely, tumor necrosis factor-alpha and interleukin-1 beta, while decreased the levels of interleukin-10, an anti-inflammatory cytokine, in the kidney. Furthermore, exposure to PbAc correlated with increased levels of pro-apoptotic markers, Bax and caspase-3, and reduced levels of the anti-apoptotic marker Bcl-2. The administration of CoQ10 alleviated the molecular, biochemical and histological changes following PbAc intoxication. Thus, CoQ10 reduces the deleterious cellular side effects of PbAc exposure due to its antioxidant, anti-inflammatory and anti-apoptotic effects.